Promising Treatment Strategies for Rett Syndrome - Kwieciński, Maciej; Makuch, Wojciech; Zaj, Natalia; Miciuda, Paulina; Kurek, Marcelina; Chrościńska-Krawczyk, Magdalena (Journal of Education, Health and Sport, 2026)
Background. Rett syndrome (RTT) is a rare, genetic neurological disease caused by a mutation of the methyl-CpG-binding protein 2 (MECP2) gene that mainly affects girls. There is no currently available causative treatment for this disease; trofinetide is the only drug dedicated to alleviating symptoms. Aim. The aim is to present potential medicines in clinical trials that have been observed to have a therapeutic benefit in the treatment of Rett syndrome. The article contains also descriptions of pathophysiology and symptoms of Rett syndrome, which can be affected by undermentioned pharmaceuticals. Material and methods. The study used Google Scholar, PubMed, and Scopus databases as its data sources. Other information was obtained from the Clinicaltrials.gov registry and database, and reports of companies conducting drug research. The literature was filtered by keywords: ‘Rett syndrome‘, ‘clinical trials’ and ‘gene therapies‘. Results. The treatment of Rett syndrome focuses on alleviating symptoms and improving the quality of life. Trofinetide is the only substance approved by the US Food and Drug Administration (FDA), which helps to reduce behavioral problems and improve social functioning. Currently, research is underway on genetic therapies, including gene replacement therapy, which may provide more effective treatment options in the future. Additionally, research is being conducted on other drugs that reduce symptoms in patients with RTT. Conclusions. Great hopes are associated with research on gene therapies, which are currently in clinical trial phases. In the future, this could bring significant benefits to patients; their implementation may not only improve aspects of the disease, such as respiratory issues, but also can result in better survival outcomes.